Potensi anti-kanker payudara tanaman songga (Strychnos lucida R.Br): Tinjauan interaksi molekuler terhadap reseptor estrogen-α in silico - Muhammad Andre Reynaldi; Arif Setiawansyah (Sasambo Journal of Pharmacy, 2022)
Songga (Styrchnos lucida R.Br) is a plant that has potential to be developed as an anti-breast cancer against. This study was conducted to predict the secondary metabolite derived from songga, which potential as anti-breast cancer through inhibition of estrogen receptor-α. A molecular docking study was carried out using Autodock Vina assisted by AutodockTool and Biovia Discovery Studio. The study used estrogen receptor-α as a protein and ten compounds from songga as ligands. The 3D structure of estrogen receptor-α and ten ligands were obtained from Protein Data Bank and the PubChem database. The result revealed that strychnine N-oxide is the compound that has the lowest free binding energy and inhibition constant with the value 9.6 kcal/mol and 0.09 µM, respectively. This indicated that strychnine N-oxide has an excellent affinity for estrogen receptor-α. Thus, this compound is predicted to inhibit the estrogen receptor-α and can be developed as anti-breast cancer. However, further investigations such as molecular dynamics simulation, in vitro and in vivo assays should be undertaken.